The Students’ Perception of the Teacher’s Facilitation in Online Group Work - Ignatius Indra Kristianto (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research examines the students’ perception of the teacher’s facilitation in online group work in English for Managers class at the Faculty of Business and Economics, Universitas Atma Jaya Yogyakarta. The study employed The Community of Inquiry (CoI) framework perspective, which consists of teaching presence, cognitive presence, and social presence. CoI has been widely employed in designing practical online courses. Thus, this descriptive qualitative research analyzed students’ perceptions of facilitation in online group work using questionnaires and interviews. The research participants were English for Managers students. They were selected since they have experience participating in online group work. The results of the study show that most of the participants have demonstrated to possess a positive perception of the teacher’s facilitation in online group work in EFM class at FBE UAJY.